2016
DOI: 10.1039/c5dt03866a
|View full text |Cite
|
Sign up to set email alerts
|

Advances in organometallic synthesis with mechanochemical methods

Abstract: Solvent-based syntheses have long been normative in all areas of chemistry, although mechanochemical methods (specifically grinding and milling) have been used to good effect for decades in organic, and to a lesser but growing extent, inorganic coordination chemistry. Organometallic synthesis, in contrast, represents a relatively underdeveloped area for mechanochemical research, and the potential benefits are considerable. From access to new classes of unsolvated complexes, to control over stoichiometries that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
278
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(284 citation statements)
references
References 102 publications
0
278
0
1
Order By: Relevance
“…We describe herein the impact of the addition of variable amounts of PEG, PEG chain length and end terminal groups, for the preparation of diverse 3,5-disubstituted hydantoins from α-amino methyl esters 1 , via an in situ intramolecular cyclization reaction of the ureido derivative B , which was obtained from N -carbamoylimidazole activated amino ester derivative A by reaction with various amines [911] (Scheme 1). Hanusa’s formalism was used to represent the reaction activated by mechanochemical energy [12]. …”
Section: Introductionmentioning
confidence: 99%
“…We describe herein the impact of the addition of variable amounts of PEG, PEG chain length and end terminal groups, for the preparation of diverse 3,5-disubstituted hydantoins from α-amino methyl esters 1 , via an in situ intramolecular cyclization reaction of the ureido derivative B , which was obtained from N -carbamoylimidazole activated amino ester derivative A by reaction with various amines [911] (Scheme 1). Hanusa’s formalism was used to represent the reaction activated by mechanochemical energy [12]. …”
Section: Introductionmentioning
confidence: 99%
“…To begin with, we demonstrated that the hydrido-Rh precursor could be synthesized under mechanochemical conditions.A sd escribed for many other organometallic complexes, [23] ball milling allowed for the straightforward synthesis of the HRh(CO)(PPh 3 ) 3 complex, as confirmed on the basis of 1 Ha nd 31 PNMR spectroscopy (Figure 2a nd Figure 3). Thehydrido-Rh species was identified at À9.8 ppm on the 1 HNMR spectrum and the Rh-P bond was revealed by the doublet at 40.0 ppm ( 1 J Rh-P = 154.9 Hz) in the 31 PNMR spectrum.…”
Section: Angewandte Chemiementioning
confidence: 64%
“…The coordinated ether in BeA' 2 ·OEt 2 proved impossible to remove without destroying the complex [11], and thus we investigated mechanochemical methods of synthesis as a means to bypass the use of ethereal solvents [14]. As detailed below, an unsolvated neutral complex was not isolated via this route, and the beryllate anion that was produced instead has structural parallels with previously described -ate complexes of Zn [15] and Sn [16].…”
Section: Methodsmentioning
confidence: 99%
“…The symbol for mechanical milling has been proposed in ref. [14]; b rystallized; limiting reagent taken into account; c Ref. [11]; d Products were observed with 9 Be NMR, ere not isolated.…”
Section: Nmr Spectroscopymentioning
confidence: 99%